Grain Refinement through Shear Banding in Severely Plastic Deformed A206 Aluminum Alloy. Issue 1 (11th September 2017) - Teymoory, Parya; Zarei‐Hanzaki, Abbas; Farabi, Ehsan; Monajati, Hossein; Abedi, Hamid Reza
Abstract : The present work is conducted to study the microstructure and texture evolutions in an as‐cast A206 aluminum alloy after applying severe plastic deformation. Toward this end, the material is severely deformed through accumulative back extrusion (ABE) technique at 200 °C and followed by assessing the room temperature mechanical properties of the products. The macro shear‐bands formation in the highly strained regions can result in grain refinement through the geometric dynamic recrystallization mechanism. A significant refinement is also characterized within the micro shear‐bands; this is attributed to the intensified substructure development and the occurrence of continuous dynamic recrystallization. The corresponding inverse pole figure maps show similar orientation for these newly refined grains with the parent ones. A random texture is produced through sub‐grain rotation to dissimilar orientation at the intersection of micro‐bands. The assessment of mechanical properties of the processed materials reveal significant increase in both yield and ultimate tensile strength values. The hardness profiles also demonstrate a relatively homogenous microstructure after three and five ABE passes holding a mean hardness value of 183 Vickers. Abstract : A206 alloy is severely deformed by accumulative back extrusion (ABE) technique at 200 °C and then the room temperature mechanical properties of the products are scrutinized. Enhancement of these properties is attributed to grain refinement that is caused by the presence of micro and macro‐shear bands in the heavily deformed regions of the material.